Pelatihan skrining tumbuh kembang bagi Guru PAUD di Kota Palembang - Lestari, Hertanti Indah; Kesuma, Yudianita; Karmila, Ariesti; Ayu, Dewi Rosariah; Akbari, Atika (Jurnal Pengabdian Masyarakat: Humanity and Medicine, 2025)
Child development disorders can affect the next stage of growth and development and can have an impact on the future. Good and proper care for children who are in the growth and development period will help children to grow healthy and be able to achieve their optimal abilities so that they can contribute better to society. The main objectives of this community service are to improve the skills of Early Childhood Education (ECE) teachers to detect early growth and development disorders, reduce the number of advanced growth and development disorders, and optimize child growth and development with early intervention. The method of service carried out in this activity is in the form of training on the use of the PRIMAKU application for 1000 ECE teachers in Palembang City and assessed using pre-test and post-test questionnaires. The results of the counseling showed an increase in results in two benchmarks, an increase in participant knowledge based on the results of the pre-test and post-test correct answers by 17.03%. Furthermore, it is expected that PAUD teachers who have attended the training can apply the use of the PRIMAKU application for early detection of growth and development disorders or delays in early childhood.